(Nk WOPROSU O ROLI OSTRIC W \TIOLOGII APPENDICITA (B/s - (NsOLOWXEW(B, (Nn(B.(Ni(B.s ((NsARATOW (B:s (NgOS(B. (NKR(B. (NIN(B-(NT MIKR(B. (NI \PID(B. (N`(B.(Nw(B. (Nrsfsr(B,s, 1927)
(NrEZ(B. (NNA FR(B. (NQZ(B.s
(NoTDELXNYJ OTTISK IZ VURNALA (B"(NwESTNIK MIKROBIOLOGII I \PIDEMIOLOGII(B", (NT(B. VI, (NWYP(B. 3, 1927 (NG(B.s
Keywords: (NaPPENDICITs -- (N|TIOLOGIQs; (NmEDICINSKAQ PARAZITOLOGIQs